2014
DOI: 10.1152/japplphysiol.01050.2013
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of hemoglobin beta-93-cysteine in posthypoxia facilitation of breathing in conscious mice

Abstract: When erythrocyte hemoglobin (Hb) is fully saturated with O2, nitric oxide (NO) covalently binds to the cysteine 93 residue of the Hb β-chain (B93-CYS), forming S-nitrosohemoglobin. Binding of NO is allosterically coupled to the O2 saturation of Hb. As saturation falls, the NO group on B93-CYS is transferred to thiols in the erythrocyte, and in the plasma, forming circulating S-nitrosothiols. Here, we studied whether the changes in ventilation during and following exposure to a hypoxic challenge were dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(104 citation statements)
references
References 57 publications
13
91
0
Order By: Relevance
“…We confirmed that total Hb concentration and blood O 2 content of the mutant strains are unchanged from wild type at baseline (room air), as reported ( Fig. S2 A and B) (19,20), and that plasma nitrite levels, a direct measure of circulatory NO production by endothelial nitric oxide synthase (eNOS), was similar in all strains (Fig. S2C).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…We confirmed that total Hb concentration and blood O 2 content of the mutant strains are unchanged from wild type at baseline (room air), as reported ( Fig. S2 A and B) (19,20), and that plasma nitrite levels, a direct measure of circulatory NO production by endothelial nitric oxide synthase (eNOS), was similar in all strains (Fig. S2C).…”
Section: Resultssupporting
confidence: 88%
“…Enhanced S-nitrosylation of a closely spaced, alternative Cys in the absence of a preferred site also has been observed in other SNO-proteins (32), including invertebrate Hb (33), and a similar shift in the site of other regulatory posttranslational modifications when preferred sites are mutated is well documented. In addition, although γ-subunits reportedly constitute only ∼1% of Hb in γβC93 and γβC93A mice (20) (percentages that we have confirmed qualitatively; Fig. S1), Hbγ concentrations nonetheless far exceed endogenous amounts of SNO-Hb, and all strains will, in fact, retain some SNO-(γ)Cys93.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…First, the expression of HVR and shortterm potentiation (STP) are absent in conscious mice with bilateral carotid sinus nerve transection (39), supporting a role of carotid body primary glomus cells/ chemoafferents in these responses. As such, the potential release of S-nitrosothiols from eNOS-positive glomus cells (11) and subsequent activation of chemoafferent terminals may contribute to the initiation of HVR, whereas S-nitrosothiols generated from red blood cell hemoglobin (see subsequent text) do not appear to be vital for initiation of the HVR (39). Second, ventilatory roll-off during the hypoxic challenge is absent in conscious GSNOR 1/2 or GSNO 2/2 mice (11), clearly suggesting that roll-off is due to enhanced catabolism of GSNO in the carotid body and/or central structures.…”
Section: Discussionmentioning
confidence: 95%